Efeito de diferentes antibióticos no processo de reparo em reimplante de dentes mantidos em leite: estudo em ratos - Maciel, Juceléia [UNESP] (2014)
A storage media use for maintanance of cell viability after pulp and periodontal ligament avulsion, if the tooth isn ́t reimplanted immediately is necessary. If the teeth are kept in a dry medium or saliva , it is recommended a topical treatment of the root with tetracycline before the reimplantation to promote pulp revascularization and periodontal ligament repair. However lack of studies on the treatment when the avulsed teeth is kept in milk . The aim of this research was to evaluate by histomorphological analysis the effect of different antibiotics in repair process of the ligament periodontal and pulp tissue of the avulsed tooth storage in milk. In forty rats Wistar (male) was carried out to upper right incisor extraction, were storage dry and/or salive and posterior reimplantation. The animals were divided according to the storage media before reimplantation: Group IM: immediate replantation. In the group DOX, the incisor was immerse in milk (4o) for 60 minutes, then it was immerse in 10 ml of solution of Doxycycline (0,05mg/ml) for 5 minutes. In the group PEN the incisor was storaged in milk (4o) associated with penicillin 10000UI plus 100mg of streptomycin for 65 minutes. In the group MS, the incisor was storaged in dry media for 65 minutes. The animals were euthanized after sixty days post-operation. The samples were processed and analyzed for histomorphometrically. It was evaluated reabsorption by substitution, inflammatory reabsorption, the periodontal ligament and their reinsertion, revascularization and pulp repair. The non-parametric Kruskall-Wallis (p> 0,05) test was used to evaluate the variables but pulp repair was analyzed by scores. Statistical analysis showed differences among groups pointed out major reabsorption on the Ms group, as well as was observed a minor inflammatory reabsorption in the Pen group, in addition to more periodontal...